ANALISIS PERBANDINGAN PENENTUAN PROFIT MARGIN PADA BANK SYARIAH DAN BUNGA PADA BANK KONVENSIONAL - Syahriyah Semaun (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
This paper examines the system of determination of the profit margin on Islamic banks and conventional banks interest. Islamic banks applying the profit margin on financing products based NCC (Natural Contract Certainty), the business agreement that provides certainty of payment, both in terms of quantity and time, such as the financing Murabaha, Ijarah, Muntahia bit Tamlik, Salam, and Istishna. Determination of the amount of the profit margin made by reference to the profit margin, that determined in the meeting of ALCO (Assets and Loans Committee) Islamic banks. Whereas in conventional banks use the system of interest, that is the price to be paid to customers (who have deposits) and the price to be paid by the customer to the bank (customers who acquire a loan). The size of interest rates on deposits and loans is strongly influenced by both, meaning both deposit and loan interest influence each other. In addition, the influence of other factors, such as guarantees, term, government policy, and profit targets.